Global corporate responsibility in domestic context: lateral decoupling and organizational responses to globalization. Issue 2 (3rd April 2017) - Lim, Alwyn
Abstract: This paper examines how the domestic reception of global corporate responsibility is significantly shaped by institutionalized differences among state, business and civil society actors in the domestic context. In the global diffusion of ideas and practices, the decoupling of global policies and domestic practice is endemic, a process that this paper argues results from competing domestic interests and orientations. I examine this process of 'lateral decoupling' in a case study of the reception of the United Nations Global Compact among corporate responsibility practitioners in the city-state of Singapore. Differences in ceremonial, pragmatic and non-adversarial orientations towards global corporate responsibility generated significant uncertainty for businesses around how to apply corporate responsibility principles. In response, businesses constructed distinct narratives: large transnational and domestic companies emphasized values, community and tradition, while small businesses focused on the competitive advantages of corporate responsibility. The paper concludes by discussing the implications of domestic institutions for mediating global principles and local outcomes.